A Proper Implementation of Water Resources Development, in Integrated and Sustainable Aspects (Two points of Critics on Disregard Implementation of The Act No.7 /2004) - Tri Hardhono; Bondan Wismandanikung (International Conference on Coastal and Delta Areas, 2015)
Due to the Act No.7/2004, there are two main purposes in Water ResourcesDevelopment (WRD), that are effectiveness and efficiently in usefulness of water, means integrated and sustainable WRD multipurposes and fight against water destroying behaviors by flood control proper implementations. Planing and Programming involving all the stake holder needs on WRD should be provided to accomplish the optimum development on related physical resources. The needsof water for irrigation, domestic and municipal purposes, industrial use, power etc, would be analysed corespond to the consumptions related to the present and future needs for populations useness in the integrated and sustainable frames. A good stake holders coordination in all aspects of quantities and qualities for all the water needs a proper execution to achieve the most important priority in WRD and strike supervision in managing project all will be the keys of success of the WRD project.In flood control planning and programming should be used the right philosophies of floods, that means based on hydrological cyclus in a river system. River systems which are consists of collecting-transporting and dispersal sub-systems, the hydrology cyclus water running through the three sub-systems from the sea, precipitated in the cathment area, erosed top soil (as in the collecting sub-system), transporting water and sediment, sedimented along the river course (as in the transporting sub-system) and water disperse to the sea include sediment which dominantly sedimented in the estuaries (as in the dispersal sub-system) are the causes in flooding. From that’s points flood control should be taken into account to have the right solutions for each sub-systems by Watershed Management, Flood Control Engineering and River & Coastal Engineering correspondly. Mapping of the needs of society means purposes of water uses such as for agricultures, domestics, industrials, waste, recreation, power etc, sources of water (rain, surface water, groundwater) availabilities, methods of development, allocation and distribution system, future developing and programming will be kept as integrated and sustaianable programme. Many interests or understandingless of WRD that may be as constraints that affected in the implementation of WRD, therefore coordination in management of water suplly on keeping water resources availability, serving-distributing, funding, planning and programming for the now and future needs will be the key of success indeed. But unfortunately there are two points in usefullness of water and flood control concepts of solutions still ought of proceeds. By these paper hopes as for critics on disregarded implementation of the Act No.7/2004, and would be improving in planning and programming in WRD and mainly as the input for the Directorate General of Water Resources Development - Department Public Works and Public Housing.